Implementation of rapid application development methods and reminder systems in the development of inventory information systems (case study: sansaquaman aquascape store) - Carrisa Aninda Putri Nugraha; Nuryanto Nuryanto; Setiya Nugroho (Universitas Muhammadiyah Magelang, 2022)
Aquascape is a new thing that is very popular in this pandemic era, the number of people who are interested in making this aquascape creates a fairly large business opportunity during this pandemic. The business of selling aquascape accessories has quite a big opportunity because of the many enthusiasts in making aquascapes. Sansaquaman is one of the shops engaged in the sale of aquascape accessories. The large number of buyers of goods in this store has resulted in several problems, such as employee errors in entering goods, calculating the stock of goods and also in ordering to suppliers. Therefore, there is a need for a system to overcome some of the problems that exist in the Sansaquaman store in order to minimize human errors, errors in calculating inventory stock and ordering goods to suppliers. In this study using the Rapid Application Development (RAD) method, so that in making the system it can be in accordance with user requests and in a short time. In this study also used 2 tests, namely the User Aceptance Test (UAT) and blackbox with the results of the User Aceptance Test from 3 users, namely 95% employees, 93% suppliers and 92% operators, while the black-box test got a value of 100%.